Influence of sedentary behavior on sleep quality in postmenopausal women in high-altitude regions of China: a cross-sectional study - Leng, Rilang; Guo, Ailin; Qian, Guoping; Mao, Sujie (Frontiers in Neurology, 2025)
ObjectiveThis study investigates the association between sedentary behavior and sleep quality among postmenopausal women residing in China’s plateau regions. Particular attention is given to moderating effects of age, body mass index (BMI), and sleep environment. This study aims to identify modifiable risk factors influencing sleep quality in this high-altitude population.MethodsThis cross-sectional study focused on postmenopausal women (aged ≥50 years, ≥12 months post-menopause) across four primary plateau regions in China: Qinghai-Tibet, Yunnan-Guizhou, Inner Mongolia, and the Loess Plateau. Sedentary behavior was evaluated with the Older Adults Sedentary Behavior Questionnaire, and sleep quality was assessed with the Pittsburgh Sleep Quality Index. Data analysis encompassed descriptive statistics, correlation analysis, multiple linear regression, and subgroup analyses.ResultsAmong the 151 participants (mean age 58.5 years), sedentary behavior was positively correlated with poorer sleep quality (r = 0.36, p < 0.001). Improvements in the sleep environment were similarly associated with better sleep quality (r = 0.29, p < 0.001). Multiple linear regression identified sedentary behavior and sleep environment as significant predictors of sleep quality, while other variables showed no significant associations. Subgroup analysis revealed age-specific effects: sedentary behavior had a strong influence on sleep quality in women under 60 years (r = 0.36, p < 0.01) but demonstrated a weaker, non-significant association in those aged 60 years or older (p = 0.062).ConclusionProlonged sedentary behavior is an independent risk factor for reduced sleep quality among postmenopausal women residing in high-altitude regions, while improvements in the sleep environment are positively associated with better sleep quality. The influence of sedentary behavior on sleep quality varies by age groups. These findings highlight the importance of tailored interventions and health policies to improving sleep quality in postmenopausal women living at high altitudes.